Life Cycle Assessment (LCA) of Carbon Emission of Garden Pavement - Peiyong WANG; Ruixing LU (Fengjing Yuanlin, 2025)
Objective With the proposal of the national “carbon neutrality” policy, various fields are exploring the mode of green, low-carbon and sustainable development. In the field of landscape architecture, a large amount of practical research has been carried out in the two aspects of enhancing urban resilience and reducing emissions and increasing sinks, both of which mainly focus on the qualitative research on study of the carbon footprints of landscape plants, soils, water bodies, green infrastructures, and green spaces over their entire life cycle. However, there exists less quantitative research on low carbon in the field of landscape engineering, which is mainly based on data from the architectural profession. The construction phase of landscape engineering is the largest part of the carbon footprint of landscape gardening, and pavement is the most carbon-emitting subcomponent of engineering construction. The current quantitative research on pavement is not enough to make a horizontal comparison of carbon emissions between different pavement materials, and there are certain deficiencies in both the parameter setting of pavement material specifications and the construction of the life cycle assessment (LCA) model in the research process, which leads to the inability to accurately judge and select low-carbon materials. Therefore, in order to assess the carbon emissions of garden pavements with different types of surface layers in pavement projects over the life cycle of such pavements, and to provide theoretical basis for the research on low-carbon emission reduction in landscape engineering, this research takes the life cycle of garden pavement projects as the theoretical basis, adopts the carbon emission factor method, constructs a calculation model for carbon emissions of garden pavements, and then calculates and screens out the optimal “carbon-friendly” materials most suitable material for garden pavements in the context of the “carbon peaking and carbon neutrality” strategy, so as to provide the theoretical basis for the low-carbon emission reduction target of landscape architecture. Methods This research selects 25 common garden pavement materials with different surface layers for calculation and evaluation of carbon emission. Firstly, the carbon emission accounting model is constructed based on the life cycle of garden pavement projects: the carbon emission factor method is adopted to calculate carbon emissions in such stages as material production, construction and transportation, maintenance and material recycling of garden pavement projects, during which the specific calculation parameters are mainly derived from the engineering practical experience, national standards and relevant research data. Secondly, after calculating the total amount of carbon emissions released during the life cycle of each type of garden pavement, the data are normalized by “carbon emission per square meter per year”, and the research results are obtained. Results The analysis of the carbon emissions of 25 types of garden pavement materials over their respective life cycle shows that, among the 25 types of garden pavements, the three types with the highest carbon emissions over their life cycle are glued stone pavement, anti-corrosion wood pavement and limestone pavement, and the three types with the lowest emissions are concrete pavement, recycled aggregate concrete pavement and pressure film art flooring. And from the perspective of the unit area and average annual carbon emission of garden pavement, the three types of garden pavements with the highest carbon emission are glued stone pavement, permeable concrete block pavement and sand-based permeable brick pavement, and the three types with the lowest emission are recycled aggregate concrete pavement, pressure film art flooring and concrete pavement. Based on the above results, the garden pavement materials that meet the requirements of low-carbon emission reduction are derived, and the following strategies for low-carbon emission reduction of garden pavements are proposed. Conclusions1) Enhance the durability of surface materials. The amount of average annual carbon emissions of surface materials over the life cycle of such materials is closely related to their durability. Therefore, enhancing the durability of materials can help prolong the service life and reduce the period of replacement and maintenance, thus achieving better cost performance. 2) Emphasize the use of concrete. Concrete is the basic structure of other pavements, and can be used directly as a pavement surface, but adding ant other surface material on top of concrete may increase carbon emissions. 3) Prioritize the use of high-strength, thin materials for garden pavements. 4) Attach importance to the life span of surface materials. The life span of different surface materials has a greater impact on the average annual carbon emissions of pavements, even greater than the thickness of pavement structure and the average annual carbon emissions of materials themselves. 5) Minimize the use of glued stone pavement. Although glued stone pavement is rich in color and can be put together freely, the carbon emission of epoxy resin binder as a chemical product contained in glued stone pavement is more than 10 times higher than that of ordinary inorganic materials. 6) Maximize the use of granular pavement. Among the 25 types of pavements, granular pavement of graded gravel surface without cementation performs best in environmental adaption, environmental protection and low carbon, and thus can be vigorously promoted for use under appropriate conditions.